Assessment of endometrial and ovarian characteristics using three dimensional power Doppler ultrasound to predict response in frozen embryo transfer cycles - Tapanainen Juha S; Järvelä Ilkka Y; Žáčková Tamara; Feyereisl Jaroslav (BMC, 2009)
Abstract Objective To evaluate whether endometrial or ovarian parameters as measured using 3D power Doppler ultrasound would predict the outcome in frozen embryo transfer (FET) cycles. Methods Thirty women with no known gynecological pathology undergoing FET were recruited. The FET was carried out in the natural menstrual cycle 3-4 days after the first positive LH test result. Blood samples for hormonal analysis were collected, and three-dimensional (3D) ultrasonographic examination was performed on the day of the FET and repeated with analysis of the total hCG one week later. Results The demographic, clinical, and embryological characteristics were similar between the pregnant (15/30) and nonpregnant groups (15/30). There were no differences between the groups in endometrial/subendometrial thickness, volume, or vascularization index (VI). The endometrial triple-line pattern was more often present in the pregnant group on the day of the FET (93.3% vs. 40.0%, 95% CI 25.5-81.2%). No differences in the ovaries were observed on the day of the FET. At the second visit, the triple-line pattern was still more often present in those patients who had conceived (91.7% vs. 42.9%, 95% CI 18.5-79.1%), and their corpus luteum was more active as judged by the rise in 17-hydroxyprogesterone and estradiol levels. No differences were observed in the dominant ovarian vasculature. Conclusions According to our results, measurement of power Doppler indices using 3D ultrasound on the day of the FET does not provide any additional information concerning the outcome of the cycle. The existence of the triple-line pattern on the day of the FET seems to be a prognostic sign of a prosperous outcome after FET. The dominant ovary in the pregnant group seems to be already activated one week after the FET.